2020
DOI: 10.3389/fcvm.2020.00128
|View full text |Cite
|
Sign up to set email alerts
|

High Inflammatory Burden: A Potential Cause of Myocardial Injury in Critically Ill Patients With COVID-19

Abstract: Background: Myocardial injury is a severe complication of novel coronavirus disease (COVID-19), and inflammation has been suggested as a potential cause of myocardial injury. However, the correlation of myocardial injury with inflammation in COVID-19 patients has not been revealed so far. Method: This retrospective single-center cohort study enrolled 64 critically ill patients with COVID-19. Patients were categorized into two groups by the presence of myocardial injury on admission. Demographic data, clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 43 publications
3
24
0
Order By: Relevance
“…Additionally, a high systemic inflammatory burden was demonstrated to be positively associated with myocardial injury in critically ill patients with COVID-19. 22 In this study, anti-inflammation therapies such as glucocorticoids or tocilizumab were used in some patients, and we found that inflammatory cytokine levels were decreased. However, related clinical investigations were not performed in this study.…”
Section: Discussionmentioning
confidence: 68%
“…Additionally, a high systemic inflammatory burden was demonstrated to be positively associated with myocardial injury in critically ill patients with COVID-19. 22 In this study, anti-inflammation therapies such as glucocorticoids or tocilizumab were used in some patients, and we found that inflammatory cytokine levels were decreased. However, related clinical investigations were not performed in this study.…”
Section: Discussionmentioning
confidence: 68%
“…There have been plenty of studies indicating that serum levels of cytokines are significantly increased in COVID-19 patients ( 3 , 4 ). Moreover, cytokine levels were associated with disease mortality and the incidence of myocardial injury ( 2 , 25 , 26 ), indicating the contributing role of cytokine storm in COVID-19 associated myocardial injury. In our population, compared with patients without myocardial injury, IL-6 levels were significantly higher in myocardial injury patients, implying the possible pathogenic role of the cytokine storm in the development of myocardial injury.…”
Section: Discussionmentioning
confidence: 99%
“…10 SARS-CoV-2 infection mainly affects the respiratory tract 11 but recently has been associated with significant multiple organ dysfunction syndrome. 12 One of the most common critical complications during COVID-19 is myocardial injury, 13,14 especially in patients with a higher inflammatory profile. 13 As the pandemic is still ongoing, it is impossible to precise the impact of SARS-CoV-2 infection in the overall population, but to the moment, COVID-19 has caused almost 1 million deaths worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…12 One of the most common critical complications during COVID-19 is myocardial injury, 13,14 especially in patients with a higher inflammatory profile. 13 As the pandemic is still ongoing, it is impossible to precise the impact of SARS-CoV-2 infection in the overall population, but to the moment, COVID-19 has caused almost 1 million deaths worldwide. Although CD affects millions, to the moment, there is no report of CD and COVID-19 coinfection in the literature.…”
Section: Introductionmentioning
confidence: 99%